Revisiting the Javanese Muslim Slametan: Islam, Local Tradition, Honor and Symbolic Communication - Mohamad Abdun Nasir (Al-Jami'ah: Journal of Islamic Studies, 2019)
Slametan, referring to a broad communal prayer, feast, and food-offering to commemorate or celebrate critical live cycles, such as birth, marriage, and death, constitutes an essential ritual for Javanese Muslims. Despite growing Islamization, in which this ritual is often renamed as tahlilan, elements of local beliefs in it remain. This study aims to re-examine the Javanese Muslim death ritual tradition and offers a new interpretation. It explores the elements of local belief and its convergence with the universal Islamic teaching and demonstrates that the Javanese norms fit the fundamental Islamic doctrines, rendering this ritual easily acceptable by the Javanese. This study concurs with the previous studies stating that this ritual paves tolerance and social integration and unites Islam and local tradition. However, this study specifically examines the meanings of the death ritual and argues that the idea of honoring predecessors and maintaining an uninterrupted symbolic communication between the alive, namely descendants, and the dead such as late parents and forebears, constitute common Javanese and Islamic values. [Slametan merupakan salah satu ritus penting bagi muslim Jawa yang berupa doa dan makan bersama serta berbagi makanan untuk memperingati atau merayakan peralihan daur hidup seperti kelahiran, pernikahan dan kematian. Meskipun Islamisasi terus berlanjut, ritus yang sering disebut juga dengan tahlilan ini masih menyisakan unsur-unsur kepercayaan lokal. Dalam artikel ini akan ditinjau kembali ritus tradisi kematian muslim Jawa dan menawarkan sebuah interpretasi baru. Tulisan ini juga mengeksplorasi unsur-unsur lokal yang menemukan titik temu dengan ajaran nilai universal dalam Islam serta menunjukkan kesepahaman norma Jawa dengan doktrin dasar Islam sehingga ritus ini mudah diterima oleh orang Jawa. Tulisan ini juga sependapat dengan kajian-kajian sebelumnya yang menyatakan bahwa ritus ini menguatkan pondasi toleransi, integrasi sosial dan penyatuan Islam dengan tradisi lokal. Meskipun demikian tulisan ini fokus pada pemaknaan ritus kematian dan berpendapat bahwa penghormatan pada leluhur serta menjaga komunikasi simbolik antara yang meninggal dan dan yang hidup, terutama yang ditinggalkan merupakan hal yang umum dalam nilai-nilai Kejawaan dan Keislaman.]